Immunometabolism of ferroptosis in the tumor microenvironment - Lupica-Tondo, Gian Luca; Arner, Emily N.; Mogilenko, Denis A.; Voss, Kelsey (Frontiers in Oncology, 2024)
Ferroptosis is an iron-dependent form of cell death that results from excess lipid peroxidation in cellular membranes. Within the last decade, physiological and pathological roles for ferroptosis have been uncovered in autoimmune diseases, inflammatory conditions, infection, and cancer biology. Excitingly, cancer cell metabolism may be targeted to induce death by ferroptosis in cancers that are resistant to other forms of cell death. Ferroptosis sensitivity is regulated by oxidative stress, lipid metabolism, and iron metabolism, which are all influenced by the tumor microenvironment (TME). Whereas some cancer cell types have been shown to adapt to these stressors, it is not clear how immune cells regulate their sensitivities to ferroptosis. In this review, we discuss the mechanisms of ferroptosis sensitivity in different immune cell subsets, how ferroptosis influences which immune cells infiltrate the TME, and how these interactions can determine epithelial-tomesenchymal transition (EMT) and metastasis. While much focus has been placed on inducing ferroptosis in cancer cells, these are important considerations for how ferroptosis-modulating strategies impact anti-tumor immunity. From this perspective, we also discuss some promising immunotherapies in the field of ferroptosis and the challenges associated with targeting ferroptosis in specific immune cell populations.